Diminishing Opportunities for Sustainability of Coastal Cities in the Anthropocene: A Review - Day, John W.; Gunn, Joel D.; Burger, Joseph Robert (Frontiers in Environmental Science, 2021)
The world is urbanizing most rapidly in tropical to sub temperate areas and in coastal zones. Climate change along with other global change forcings will diminish the opportunities for sustainability of cities, especially in coastal areas in low-income countries. Climate forcings include global temperature and heatwave increases that are expanding the equatorial tropical belt, sea-level rise, an increase in the frequency of the most intense tropical cyclones, both increases and decreases in freshwater inputs to coastal zones, and increasingly severe extreme precipitation events, droughts, freshwater shortages, heat waves, and wildfire. Current climate impacts and are already strongly influencing natural and human systems. Because of proximity to several key warming variables such as sea-level rise and temperature stress, coastal cities are a leading indicator of what may occur worldwide. Climate change alone will diminish the sustainability and resilience of coastal cities, especially in the tropical-subtropical belt, but combined with other global changes, this suite of forcings represents an existential threat, especially for coastal cities. Urbanization has coincided with orders of magnitude increases in per capita GDP, energy use and greenhouse gas emissions, which in turn has led to unprecedented demand for natural resources and degradation of natural systems and more expensive infrastructure to sustain the flows of these resources. Most resources to fuel cities are extracted from ex-urban areas far away from their point of final use. The urban transition over the last 200 years is a hallmark of the Anthropocene coinciding with large surges in use of energy, principally fossil fuels, population, consumption and economic growth, and environmental impacts such as natural system degradation and climate change. These energy sources enabled and underwrote Anthropocene origins and fueled the dramatic expansion of modern urban systems. It will be difficult for renewable energy and other non-fossil energy sources to ramp up fast enough to fuel further urban growth and maintenance and reverse climate change all the while minimizing further environmental degradation. Given these trajectories, the future sustainability of cities and urbanization trends, especially in threatened areas like coastal zones in low-income countries in the tropical to sub-tropical belt, will likely diminish.